(untitled) (UMRAN - Journal of Islamic and Civilizational Studies, 2026)
This article analyses the Islamic curatorial approach to the management of artifacts, sacred objects, and religious spaces, grounded in the principles of adab (etiquette), maqasid al-shariah (higher objectives of Islamic law), and the epistemology of tawhid (divine unity). It highlights the fundamental differences between secular Western curatorial models and Islamic perspectives that emphasize sanctity, devotional function, and spiritual responsibility. The analysis includes a typology of sacred objects in Islam, a value-based curatorial framework, and the urgent need to develop ethical codes, professional training modules, and Islamic curatorial research institutions. The article proposes an interdisciplinary and context-sensitive model as a meaningful alternative for building a just, dignified, and spiritually conscious Islamic curatorial system.